Swedish treebank - Språkbanken Text (University of Gothenburg, 2025)
A Swedish treebank built from recycled language resources

The Swedish treebank has come about through work by researchers in the Universities at
Uppsala (Computational Linguistics, Department of
Linguistics and Philology) and Växjö
(The Language Technology research
group in the School of Mathematics and Systems Engineering). The treebank is the
result of the harmonization of the linguistic information in two existing Swedish
language resources:

Talbanken, a corpus of Swedish written and transcribed spoken
language from the 1970s, manually annotated with syntactic information according
to a traditional Scandinavian approach

SUC2 (Stockholm Umeå Corpus), a morphosyntactically annotated
(all corpus words are tagged with part of speech and lemma), balanced corpus
of published Swedish written language from the 1990s

The harmonization process in brief has been that Talbanken has been annotated
with the morphosyntactic tags used in SUC in a semiautomatic process, and both
Talbanken and SUC have been automatically syntactically annotated with a phrase
structure version of Talbanken's original syntax analysis. This means that
we can expect errors in the syntactic annotation, particularly in SUC.
A preliminary evaluation of the annotation, presented at
a post-conference
workshop at SLTC 2008, shows that the syntactic annotation is still very
useful in corpus-linguistic investigations.

Format, license and distribution
Format
The Swedish treebank is distributed in the TIGER-XML format, so that the
freely available TIGERSearch tool can be used with it. TIGERSearch can be downloaded
from Institut
für Maschinelle Sprachverarbeitung at the Universitety of Stuttgart.

License
The treebank part - i.e., the added syntactic annotations - of
the Swedish treebank, is free, under an open source license.

Talbanken is freely available for research and education purposes, it can
be downloaded here

SUC requires that each user signs an individual license agreement with
the Department of Linguistics, Stockholm University. As of 1st December, 2008, licensing of
SUC is entrusted to Språkbanken, University of Gothenburg. The license agreement can
be downloaded in
pdf format here. Read more about SUC2 and SUC3 here

In order to get access to SUC (and thereby to the Swedish treebank), you are required to
print out the license agreement form, sign it and send it by ordinary mail to

SUC-licens
Språkbanken
Institutionen för svenska, flerspråkighet och språkteknologi
Göteborgs universitet
Box 200
SE-405 30 Göteborg
Sweden

Upon receipt and approval of the agreement, we will contact you by email
with downloading instructions.

Distribution
The Swedish treebank is distributed by Språkbanken, University of Gothenburg.
See the preceding section for instructions, or contact us for more information
by emailing sb-info@svenska.gu.se.

If you have a SUC license already, you will get downloading instructions
and password from us.
Others will first need to sign a SUC license agreement (see above).

References
If you wish to cite the Swedish treebank in a paper, please use the following reference:

Joakim Nivre, Beáta Megyesi, Sofia Gustafson-Capková, Filip Salomonsson and Bengt Dahlqvist (2008) Cultivating a Swedish Treebank
In: Nivre, Dahllöf, and Megyesi (Eds), Resourceful Language Technology: Festschrift in Honor of Anna Sågvall Hein, pp111–120.
Uppsala: Acta Universitatis Upsaliensis.
http://urn.kb.se/resolve?urn=urn:nbn:se:uu:diva-8933

You can give this Språkbanken page as its download location.

En svensk trädbank med återanvändning av existerande resurser

Den svenska trädbanken är resultatet av ett arbete som har utförts av forskare vid universiteten i
Uppsala (Datorlingvistik, Institutionen för lingvistik och filologi) och Växjö
(Språkteknologigruppen vid
Matematiska och systemtekniska institutionen). Trädbanken är resultatet av en harmonisering
av den lingvistiska informationen i två befintliga
svenska språkresurser:

Talbanken, en korpus med svenskt skriftspråk och transkriberat
talspråk från 1970-talet, som är försedd med manuellt utförda syntaktiska analyser
enligt en traditionell nordistisk modell (en slags utvidgad fältanalys à la
Diderichsen)

SUC (Stockholm Umeå Corpus), en morfosyntaktiskt analyserad
(försedd med ordklassetiketter och grundformer på alla korpusens ord) balanserad
korpus över publicerat svenskt skriftspråk från 1990-talet

I korthet har harmoniseringen gått till så att Talbanken försetts med SUC:s
ordklassetiketter i en halvautomatisk process, och både Talbanken och SUC har
försetts med en frasstrukturversion av Talbankens syntaktiska annotation.
Den senare processen har varit helautomatisk, vilket innebär att man kan
förvänta sig felaktigheter i den syntaktiska annotationen, särskilt i SUC-korpusen.
En preliminär utvärdering av annotationen presenterad vid
en workshop i samband med
SLTC 2008 visar att den syntaktiska annotationen ändå är till mycket god hjälp vid
korpuslingvistiska undersökningar.

Format, licens och distribution
Format
Den svenska trädbanken distribueras i ett format som kallas TIGER-XML, så att den
ska kunna användas med det fritt tillgängliga sökverktyget TIGERSearch, som kan
laddas ner
från Institut
für Maschinelle Sprachverarbeitung vid universitetet i Stuttgart.

Licens
Trädbanksdelen - d.v.s. de nytillagda syntaktiska annotationerna - av
den svenska trädbanken är helt fri, med en öppen källkodslicens.

Talbanken är fritt tillgänglig för forskning och undervisning. Den kan laddas ned här
SUC kräver att varje användare tecknar en individuell licens med
Institutionen för lingvistik vid Stockholms universitet. Från och med den 1/12 2008
är licensieringen
av SUC delegerad till Språkbanken vid Göteborgs universitet. SUC-licensavtalet kan laddas
ner i pdf-format här. Läs mer om SUC2 och SUC3 här

För att erhålla SUC (och därmed den svenska trädbanken) behöver du skriva ut och skriva under
licensavtalet och sedan skicka det till

SUC-licens
Språkbanken
Institutionen för svenska, flerspråkighet och språkteknologi
Göteborgs universitet
Box 200
405 30 Göteborg

Därefter återkommer vi per epost med nerladdningsinstruktioner.
Distribution
Den svenska trädbanken distribueras av Språkbanken. Se instruktioner i föregående
avsnitt eller kontakta oss för mer information genom att eposta sb-info@svenska.gu.se.

Den som redan har skrivit
på en SUC-licens får direkt nedladdningsadress och lösenord från oss. Övriga behöver först
skriva under ett licensavtal för SUC (se ovan).

Referenser
Om du vill citera Svensk trädbank i en artikel rekommenderar vi att du använder följande referens:

Joakim Nivre, Beáta Megyesi, Sofia Gustafson-Capková, Filip Salomonsson and Bengt Dahlqvist (2008) Cultivating a Swedish Treebank
In: Nivre, Dahllöf, and Megyesi (Eds), Resourceful Language Technology: Festschrift in Honor of Anna Sågvall Hein, pp111–120.
Uppsala: Acta Universitatis Upsaliensis.
http://urn.kb.se/resolve?urn=urn:nbn:se:uu:diva-8933

Ange gärna den här sidan på Språkbanken som nedladdningssajt.
Svensk trädbank
Keywords: Language Technology (Computational Linguistics); corpus; Natural Language Processing; Språkbehandling och datorlingvistik